Pengauditan Sistem Informasi E-Learning Menggunakan Framework COBIT 5 - Nurhaliza; Musthofa Akmal Syahputra; Amelia Putri; Praja Sukma Malengga (CV. ITTC INDONESIA, 2024)
E-learning has become an important component in the world of education. An effective and efficient e-learning information system is needed to support the teaching and learning process. Auditing e-learning information systems is important to ensure that the system is running well and meets its objectives. This research aims to audit e-learning information systems using the COBIT 5 framework. COBIT 5 is a comprehensive and internationally recognized IT governance and control framework. This research uses a qualitative method with a case study approach. Data was collected through interviews, observation and documentation analysis. The research results show that the maturity level of the e-learning information system is still at level 3 (Defined Process).